Conflict Resolution: the Truncated Zoning Arrangement and the Buhari Political Tsunami in Nigeria - TERWASE, ISAAC TERUNGWA; ABDUL-TALIB, ASMAT-NIZAM; ZENGENI, KNOCKS TAPIWA (Universitas Muhammadiyah Yogyakarta, 2015)
The Nigerian Fourth Republic ushered in a demo-cratically elected government in 1999 that paved way for the civilians to take over government after a long period of military rule in Nigeria. This made the political parties to project their candidates for contest in occupying the political positions at the federal, states and local government levels. Thus, such projection through the ruling political party that won the election in 1999 known as the People’s Democratic Party (PDP), went into zoning arrange-ment that could give the country’s six geopolitical zones a place for participation in the administration of the country. This arrangement coordinated the highest positions such as the President, Vice-Presi-dent, President of the Senate, Speaker of the House of Representatives, Secretary to the Government of the Federation, and Chairman of the ruling party. However, such arrangements were only practiced from 1999 to 2011. The zoning arrangements were trun-cated in 2011, which led to conflict in the Northern part of the country. The objective of the study there-fore, is to examine the consequences of the trun-cated zoning arrangement and lessons from the Buhari Political tsunami in 2015 general elections in Nigeria, with interest on how to resolve such con-flicts that emanated. The study made use of qualita-tive research and the review of previous literature as sources of data collection. The findings revealed that, many people were killed during the years 2011-2015 under study; both private and public properties were also destroyed. This study recom-mends constitutional approach regarding the zoning formula to accom-modate all the six geopolitical zones in Nigeria in order to resolve the conflicts therein.